2002
DOI: 10.1145/820127.820183
|View full text |Cite
|
Sign up to set email alerts
|

An experience in integrating automated unit testing practices in an introductory programming course

Abstract: Unit testing is one of the core practices in the Extreme Programming lightweight software development method, and it is usually carried out with the help of software frameworks that ease the construction of test cases as an integral part of programming tasks. This work describes our first results in studying the integration of automated unit testing practices in conventional 'introduction to programming' laboratories. Since the work used a classical procedural language in the course's assignments, we had to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 4 publications
2
25
0
4
Order By: Relevance
“…Garcia et al [8] report that teaching beginning students in a test-driven manner resulted in only 10% of students choosing to use automated tests. However, there were several differences in their approach that may account for why so few students chose to use TDD.…”
Section: Few Choosing Tddmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia et al [8] report that teaching beginning students in a test-driven manner resulted in only 10% of students choosing to use automated tests. However, there were several differences in their approach that may account for why so few students chose to use TDD.…”
Section: Few Choosing Tddmentioning
confidence: 99%
“…These very simple first steps are to help the student build confidence and to not be overwhelmed too early. This will attempt to break down some of the initial resistance to TDL other studies have found to be common in beginning students [9,8].…”
Section: Step 1: Introduction To Arraysmentioning
confidence: 99%
“…Barriocanal [13] documented an experiment in which students were asked to develop automated unit tests in programming assignments. Christensen [14] proposes that software testing should be incorporated into all programming assignments in a course, but reports only on experiences in an upper-level course.…”
Section: Related Workmentioning
confidence: 99%
“…Despite such limitations, Barriocanal [3] has shown that the teaching of testing earlier can improve the quality of the code implemented and can ease the learning process, both of testing and of programming. Barriocanal has also investigated if the learners are keen on to perform tests in their programs.…”
Section: Some Issues On Teaching Programming and Testingmentioning
confidence: 99%
“…One of the initiatives which has been investigated refers to the introduction of testing concepts in conjunction with programming foundations in introductory CS courses [3]- [6]. Programming foundations is not an easy subject to be taughtmany students have difficulties understanding the abstract concepts of programming [7] and have a wrong view about the programming activity [6].…”
Section: Introductionmentioning
confidence: 99%